2014
DOI: 10.1371/journal.pone.0108998
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Comorbidities and Their Impact on Hospital Management and Short-Term Outcomes in Vietnamese Patients Hospitalized with a First Acute Myocardial Infarction

Abstract: BackgroundCardiovascular disease is one of the leading causes of morbidity and mortality in Vietnam. We conducted a pilot study of Hanoi residents hospitalized with a first acute myocardial infarction (AMI) at the Vietnam National Heart Institute in Hanoi for purposes of describing the prevalence of cardiovascular (CVD) and non-CVD comorbidities and their impact on hospital management, in-hospital clinical complications, and short-term mortality in these patients.MethodsThe study population consisted of 302 Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
2
11
1
1
Order By: Relevance
“…This, in part, supports earlier findings [ 14 , 18 ]. However, in contrast to our findings others report depression [ 18 ] and GI bleeding/ulcer [ 19 ] to be diagnosed in a significant proportion of the studied population. Radovanovic et al studied over 30 000 patients who were enrolled into the AMIS Plus registry and found that 7%, 6%, and 2% of patients were reported to have kidney disease, lung disease, and GI ulcer respectively [ 15 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This, in part, supports earlier findings [ 14 , 18 ]. However, in contrast to our findings others report depression [ 18 ] and GI bleeding/ulcer [ 19 ] to be diagnosed in a significant proportion of the studied population. Radovanovic et al studied over 30 000 patients who were enrolled into the AMIS Plus registry and found that 7%, 6%, and 2% of patients were reported to have kidney disease, lung disease, and GI ulcer respectively [ 15 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, patients with three or more noncardiac comorbidities had markedly increased odds of dying during hospitalization compared to those with no noncardiac comorbidities previously diagnosed [ 14 ]. In contrast to the previously mentioned analyses, but similarly to our study, Nguyen et al found similar in-hospital mortality rates irrespective of the number of comorbid conditions 6.8%, 5.5%, and 9.7% for 0, 1, and 2 or more comorbidities respectively P=0.53) [ 19 ]. Possible explanations for the lack of impact of multimorbidity on in-hospital mortality in our cohort include: i) the effect of T2DM on in-hospital mortality, (ii) similar age, (iii) similar rate of cardiogenic shock and multivessel coronary artery disease, (iv) similar time from symptom onset, and (v) similar rate of successful PCI among others.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Treatment cost of the first and following years after the first acute MI event was calculated based on expert opinion. We applied a proportion of 68.5% patients with a first acute MI who had percutaneous coronary intervention or coronary artery bypass surgery [ 31 ] in the first-year treatment. We also assumed that there was no specific treatment or rehabilitation for stroke patients after acute events, which is common in Vietnam, where rehabilitation and long-term care is done by family members.…”
Section: Methodsmentioning
confidence: 99%
“…Cares y cols hallaron en su estudio que los pacientes con un puntaje más alto en el índice de Charlson no presentaron estadías hospitalarias más prolongadas (1), al igual que nosotros que no encontramos asociación entre la variable comorbilidades y la estancia hospitalaria prolongada en adultos mayores. Sin embargo, Nguyen y Teo en sus estudios e n c o n t r a r o n q u e l o s p a c i e n t e s c o n comorbilidades tendían a experimentar a una estancia hospitalaria prolongada (12,13). Otro estudio de mostró que las comorbilidades están asociadas con una población de pacientes ancianos con estadía hospitalaria prolongada (14).…”
Section: Discussionunclassified